South Africa's EIA Screening Tool: A preliminary study of how users perceive its accuracy and utility. Issue 2 (4th March 2023) - Lambrecht, Michael; Sowman, Merle; Day, Kirsten
ABSTRACT: Recognising the value of GIS in screening environmental impacts, the South African government has introduced a web-based Screening Tool as a mandatory part of the EIA application process. The Tool draws on numerous databases to depict sensitive attributes of proposed development sites. Enforcement of the Tool has implications for how EIAs are conducted, in terms of both scope and cost. In this paper we present the results of preliminary research into user perceptions of the accuracy and utility of the Tool. Findings from a national survey and several semi-structured interviews show that most users are not confident that the Tool accurately assigns sensitivity ratings according to various environmental themes. Notwithstanding this finding, overall opinion is that the Tool has potential to improve the scientific robustness of the EIA process. It is recommended that practitioners and specialists are involved in further development of the Tool to increase accuracy of the sensitivity ratings. We conclude more generally that integration of GIS can compensate for knowledge gaps and enhance the scientific veracity of EIA.